EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR DALAM MENULIS PUISI PADA SISWA MADRASAH IBTIDAIYAH HAURKOLOT INDRAMAYU TAHUN 2019 - Satiyem Satiyem; Moch. Hasyim Fanirin (Bajang Institute, 2022)
The intructional of Indonesian language and its literature are aimed to improve the sudnts’ ability for both verbal and written comunication. It includes four aspects of skill. Those are listening, speaking, reading, and writing. The use of pictures media is the solution for improving writing skills particularly in writing poetry. The aim of this study is to analyze the effectiveness of pictures media. This research was conducted at 4th grade primary school of Madrasah Ibtidaiyah Haurkolot Indramayu in 2nd semester the theacademic year 2018/2019. The methodology used in this study was experimental. The subject of the study were sixteen students of fourth grader (eight studnts for each males and females). The data collection techniques applied were observation, interviews and poetry writing test. This research showed that before the experimental treatment of applying the pictures media for learning Indonesian lguage, there were only two students from sixteen or 12,5 % obtained hihgh score however after te treatment, eleven students or 68,75% acquired good score. The study concuded that the utlization of pictures medi I writig poetry was effective.